Acinetobacter baumannii: Mechanisms of Antimicrobial Resistance - N. E. Barantsevich; L. V. Ivanova; E. P. Barantsevich (Антибиотики и Химиотерапия, 2025)
Gram-negative non-fermenting bacteria Acinetobacter baumannii are a common cause of severe complications (pneumonia, bacteremia, sepsis) in the clinic of internal diseases, especially in patients with weakened immune system: 3,2% of bacteremia and sepsis cases are associated with A. baumannii, with mortality rate 26–91%. A. baumannii has the ability to rapidly acquire antimicrobial resistance. In recent decades, strains with multiple resistance to antimicrobial drugs have emerged, including beta-lactams, including carbapenems, aminoglycosides, and fluoroquinolones, which are the drugs of choice in the treatment of severe hospital infections caused by Gram-negative microorganisms. Globally, about 45% of A. baumannii isolates are multidrug-resistant, with multidrug resistance reaching 90% in the Middle East, Southern Europe, and North Africa, and 60% in China. The prevalence of polyresistant strains of A. baumannii in patients with nosocomial pneumonia associated with mechanical ventilation is estimated at 80%. The main mechanisms of antimicrobial resistance of the pathogen are impaired permeability of the cell wall to antibiotics as a result of modification of porin proteins, activation of eﬄux pump systems, production of enzymes that destroy antibacterial drugs, and biofilm formation. The review examines the molecular basis of the formation of resistance to antibacterial drugs in A. baumannii.